Changes in Body Fat and Weight After a Breast Cancer Diagnosis: Influence of Demographic, Prognostic, and Lifestyle Factors - Melinda L. Irwin; Anne McTiernan; Richard Baumgartner; Kathy B. Baumgartner; Leslie Bernstein; Frank D. Gilliland; Rachel Ballard‐Barbash (2005)
Purpose Obese women and women who gain weight after a breast cancer diagnosis are at a greater risk for breast cancer recurrence and death compared with lean women and women who do not gain weight after diagnosis. In this population-based study, we assessed weight and body fat changes from during the first year of diagnosis to during the third year after diagnosis, and whether any changes in weight and body fat varied by demographic, prognostic, and lifestyle factors in 514 women with incident Stage 0-IIIA breast cancer. Methods Patients were participants in the Health, Eating, Activity, and Lifestyle (HEAL) study. Weight and body fat (via dual-energy x-ray absorptiometry scans) were measured during the baseline visit and 2 years later at a follow-up visit. Analysis of covariance methods were used to obtain mean weight and body fat changes adjusted for potential cofounders. Results Women increased their weight and percent body fat by 1.7 ± 4.7 kg and 2.1% ± 3.9%, respectively, from during their first year of diagnosis to during their third year of diagnosis. A total of 68% and 74% of patients gained weight and body fat, respectively. Greater increases in weight were observed among women diagnosed with a higher disease stage, younger age, being postmenopausal, and women who decreased their physical activity from diagnosis to up to 3 years after diagnosis (P for trend < .05). Conclusion Weight and body fat increased in the postdiagnosis period. Future research should focus on the effect of physical activity on weight and fat loss and breast cancer prognosis.